PENGARUH EARNING PER SHARE TERHADAP HARGA SAHAM - Dini Arifian; Damyati Hardi (The Asia Pacific Journal Of Management Studies, 2017)
This research was conducted at Plantation Sub Sector companies listed on the Indonesia Stock Exchange (IDX). The purpose of this study is to find out how the condition of earnings per share and share prices in plantation sub-sector companies every year and to find out how much influence per share per share on stock prices.The method used in this research is associative hypothesis testing method. The data collection technique is documentation observation. By doing a simple linear regression analysis, Correlation Analysis, Correlation Coefficient Analysis and Hypothesis Testing which is calculated using SPSS V.20.The level of strength of the relationship (correlation) between the variable earnings per share with stock prices is equal to 0.906 or very strong. The correlation coefficient is positive, that is 0.906, Rquer value is 0.821. This value implies that the effect of earnings per share on stock prices is 82.1%. Based on the results of the t test, it is known that the significant value or Sig. (2-tailed) is 0,000, because the Sig value (2-tailed) is 0,000 <or more smaller than 0.05, it means that there is a significant relationship between variable earnings per share with variable stock prices. with a simple linear regression equation Y = 1,487 + 0,886 X.Based on the results of data analysis, it can be concluded that earnings per share has a positive and significant effect on the share prices of plantation sub-sector companies listed on the Indonesian Securities Exchange 2011-2016. this research is expected to be used as a material consideration for making decisions in stock investing.